ODAD1 variants resulting from splice-site mutations retain partial function and cause primary ciliary dyskinesia with outer dynein arm defects - Zhou, Nannan; Liang, Weilin; Zhang, Yanzhu; Quan, Guoli; Li, Ting; Huang, Siqing; Huo, Yating; Cui, Haiyan; Cheng, Yuanxiong (Frontiers in Genetics, 2023)
Primary ciliary dyskinesia (PCD) is a genetically heterogeneous disorder caused by defects in motile ciliary function and/or structure. Outer dynein arm docking complex subunit 1 (ODAD1) is an important component of the outer dynein arm docking complex (ODA-DC). To date, 13 likely pathogenic mutations of ODAD1 have been reported. However, the pathogenesis of ODAD1 mutations remains elusive. To investigate the pathogenesis of splice-site mutations in ODAD1 discovered in this study and those reported previously, molecular and functional analyses were performed. Whole-exome sequencing revealed a compound mutation in ODAD1 (c.71-2A>C; c.598-2A>C) in a patient with PCD, with c.598-2A>C being a novel mutation that resulted in two mutant transcripts. The compound mutation in ODAD1 (c.71-2A>C; c.598-2A>C) led to aberrant splicing that resulted in the absence of the wild-type ODAD1 and defects of the outer dynein arm in ciliary axonemes, causing a decrease in ciliary beat frequency. Furthermore, we demonstrated that the truncated proteins resulting from splice-site mutations in ODAD1 could retain partial function and inhibit the interaction between wild-type ODAD1 and ODAD3. The results of this study expand the mutational and clinical spectrum of PCD, provide more evidence for genetic counseling, and offer new insights into gene-based therapeutic strategies for PCD.